Ecological and geographical, social and economic conditionality of the desease of the malignant new growths of the population in mountain areas of Republic Dagestan - A. G. Gasangadzhiyeva; P. I. Gabibova (Юг России: экология, развитие)
Epidemiological features, the basic tendencies, dynamics and structure of the reasons, territorial features malignant neoplasm morbidity during with 1991 for 2005 are revealed. Is revealed a number of risk factors, probably, promoting occurrence and development of malignant new growths in investigated areas.